Making and Breaking Borders - Bal, Mieke (Artium Quaestiones, 2024)
The concept of border or boundary has two ambiguities to deal with, if it is to serve a useful intellectual purpose in art and art history. One is to decide whether a border is a line, one that divides, separates, and thus can lead to competition, even to animosity; or whether it constitutes a space within which negotiating can happen. The other ambiguity concerns the differences, in style, period, national background, religious or sexual orientation, between artworks we contemplate in exhibitions, for example. That also raises the question if and how such differences can bridge the gaps and connect the artworks. I propose to take one case, a scene from my installation Don Quijote: Sad Countenances (from 2019), in which the knight errant and his squire have a conversation, seated at a café terrace, and probe their differences in social status, educational level, a probing that threatens their friendship and thereby establishes a new boundary. The scene is ambiguous in that the two sit next to each other in seeming equality, whereas their conversation itself establishes hierarchical relationships, thus making a border. Yet after that tense moment, they revert to their previous, friendly being-together. The border as a dividing line they were building up breaks down when the differences fade away, as the actress playing Sancho reverts to the French of her “boss”. With this making and breaking of borders, the two figures manage to share insights they would not have had before. The conversation scene is only eight minutes long, and establishes differences subsequently fading. There is very little acting, and there is nothing like a beautiful landscape. The differences between the languages they speak (French and Spanish) and the disagreements between them vanish in the face of the impossibility to maintain borders as lines, and instead produce that space of negotiation within which relationships can be restored. This enables the dynamic of empathy between the figures but also, and more importantly, between the fictional conversation and the real visitors.